Antibiotic Resistance of Staphylococcus aureus Strains—Searching for New Antimicrobial Agents—Review - Michał Michalik; Adrianna Podbielska-Kubera; Agnieszka Dmowska-Koroblewska (Pharmaceuticals)
Inappropriate and excessive use of antibiotics is responsible for the rapid development of antimicrobial resistance, which is associated with increased patient morbidity and mortality. There is an urgent need to explore new antibiotics or alternative antimicrobial agents. S. aureus a commensal microorganism but is also responsible for numerous infections. In addition to innate resistance to β-lactam antibiotics, S. aureus strains resistant to methicillin (MRSA) often show resistance to other classes of antibiotics (multidrug resistance). The advancement of phage therapy against MRSA infections offers a promising alternative in the context of increasing antibiotic resistance. Therapeutic phages are easier to obtain and cheaper to produce than antibiotics. However, there is still a lack of standards to ensure the safe use of phages, including purification, dosage, means of administration, and the quantity of phages used. Some bacteria have developed defense mechanisms against phages. The use of phage cocktails or the combination of antibiotics and phages is preferred. For personalized therapy, it is essential to set up large collections to enable phage selection. In the future, the fight against MRSA strains using phages should be based on a multidisciplinary approach, including molecular biology and medicine. Other therapies in the fight against MRSA strains include the use of endolysin antimicrobial peptides (including defensins and cathelicidins). Researchers’ activities also focus on the potential use of plant extracts, honey, propolis, alkaloids, and essential oils. To date, no vaccine has been approved against S. aureus strains.